Kantowski–Sachs Model with a Running Cosmological Constant and Radiation - Vinícius Guilherme Oliveira; Gil de Oliveira Neto; Ilya L. Shapiro (Universe, 2024)
The simplest anisotropic model of the early universe is the one with two conformal factors, which can be identified as the Kantowski–Sachs metric, or the reduced version of the Bianchi-I metric. To fit the existing observational data, it is important that the anisotropy is washed out in the early stage of the evolution. We explore the possible effects of the running cosmological constant on the dynamics of isotropy in the case of space filled by radiation.